Influência da variação da carga de treino resistido, sob o método de circuito, sobre o gasto energético e cinética da creatina quinase em homens adultos treinados e destreinados - Teixeira, Jeferson Américo Ancelmo (2017)
Resistance training is characterized by the action against a resistance leading to a muscular stress, which can be generated by different methods, be they maximum, until the concentric failure or submaximal, finalized series before the concentric failure. In relation to the energy expenditure (EE), the literature suggests that there may be a point of proximity of the concentric failure in which the energy metabolized to the execution of each repetition becomes higher, even with the maintenance of the intensity. Another important aspect is the level of muscle injury determined by creatine kinase (CK), an indirect marker of muscle injury induced by exercise, however, the literature does not present studies comparing the blood CK response to RT with and without concentric failure. soon this study proposed to analyze the GE and the muscular damage in the conditions according to the protocol of 3 sessions of training with different volumes and weight of 20RM in 9 men trained and untrained. The energetic GE was measured by the collection of expired gases (aerobic component) and the anaerobic component was determined by the product of lactate variation (Δlac) by body weight, with Total expenditure being the sum of these two. Kinetics of blood CK were determined in collections performed before and 24h, 48h and 72h after each session. All data were analyzed using the software Statistic 7, normality was analyzed by the Kolmogorov- Smirnov test e homogeneity by Levene, a two-way analysis of variance (ANOVA) with Tukey post-hoc was used for parametric variables and nonparametric variables were analyzed by Kruskal Walls ANOVA. Comparisons between groups were made with t student test. Significance level was established at 5% (p<0.05). The IFMR was significantly higher in all exercises for the trained group. In the 3 training sessions, trained group performed the higher training volume. Regarding EE, the untrained group has no difference between the 3 sessions while the trained group had higher EE in the 20rep session compared to the other sessions. CK kinetics peaked at 48h for all groups and training sessions and the highest values were found after 16rep for the untrained and 20rep for the trained. Since the CK / rep was higher in the sessions closer to the concentric failure.The result of the present study showed that it is not necessary for the untrained individuals to perform maximal training to obtain higher EE because they lose efficiency during training, which may have been due to a failure in the inter and intramuscular interaction that occurs through neural adaptation to training. For the trained individuals, the increase in the number of repetitions per series is an efficient strategy for the increase of the EE, since there is an increase of the expense that is closer to the failure, which was observed when analyzing the EE / rep. The CK concentration analysis also showed that there is no difference in the level of training, but it is larger the closer to failure. In addition, it is important to observe the peak of 48h for prescription of similar protocols.